Revealing Classroom Culture in History Learning: An Ethnographic Approach at SMAN 1 Leuwilang Bogor - Meida Rahmalia; Sifa Mutiasari; Leli Yulifar (Historia, 2027)
This research was motivated by the dominance of history learning that focuses on memorization, resulting in low student participation in the learning process. This study aims to reveal classroom culture in history learning through an ethnographic approach in class XI.8 of SMAN 1 Leuwiliang. The research used a qualitative approach with an ethnographic method. The research subjects consisted of history teachers and students of class XI.8 selected purposively. Data were collected through observation, in-depth interviews, and documentation, while data analysis used data reduction, data display, and conclusion drawing. The results showed that the classroom culture formed was active, interactive, and participatory. The teacher acted as a facilitator who encouraged dialogue, discussion, and the use of varied learning media. Open interaction between teachers and students created a conducive learning environment and improved students’ motivation, critical thinking, and historical awareness in history learning.